Power Fan Design of Blended-Wing-Body Aircraft with Distributed Propulsion System - Yuan Jia; Jinye Li; Jianghao Wu (International Journal of Aerospace Engineering)
A blended-wing-body aircraft has the advantages of high lift-to-drag ratio, low noise, and high economy compared with traditional aircraft. It is currently a solution with great potential to become a future civilian passenger aircraft. However, most airplanes with this layout use distributed power, and the power system is on the back of the fuselage, with embedded or back-supported engines. This type of design causes the boundary layer suction effect. The boundary layer ingestion (BLI) effect can fill the wake of the aircraft and improve the propulsion efficiency of the engine. However, it causes huge design difficulties, especially when the aircraft and the engine are strongly coupled. In this paper, an aircraft with a coupled engine configuration is studied. The internal and external flow fields are calculated through numerical simulation. A realistic calculation model is obtained through the coupling of boundary conditions. On the basis of the influence of the external flow on the internal flow under the coupled condition, the influence of the BLI effect on the aerodynamic performance of the fan is investigated.